2018
DOI: 10.1096/fj.201800108r
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal short‐chain fructooligosaccharides program intestinal microbiota and improve enteroinsular axis function and inflammatory status in high‐fat diet‐fed adult pigs

Abstract: Perinatal nutrition programs physiologic and metabolic functions, with consequences on the susceptibility to develop metabolic diseases in adulthood. The microbiota represents a key factor of such programming. We investigated whether perinatal prebiotic [short-chain fructooligosaccharides (scFOS)] supplementation improved adult metabolic health in association with microbiota changes in pigs used as human model. Sows were supplemented with scFOS or not during the end of gestation and the entire lactation, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 58 publications
(81 reference statements)
3
33
1
Order By: Relevance
“…The impact of prebiotic (CTRL- vs. PREB) was analyzed on mononuclear immune cells extracted from jej-PP at PND49 and PND90 and from il-PP at PND10, PND21, PND49 and PND90. We used immune cells from il-PP and jej-PP at PND90, as we recognized the effects of perinatal maternal scFOS on offspring immune system, long after his birth [ 8 , 10 ]. Previous studies have demonstrated that the intestinal absorption of DON takes mainly place in the jejunum directly from the intestinal lumen to the apical side of the intestinal epithelium [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of prebiotic (CTRL- vs. PREB) was analyzed on mononuclear immune cells extracted from jej-PP at PND49 and PND90 and from il-PP at PND10, PND21, PND49 and PND90. We used immune cells from il-PP and jej-PP at PND90, as we recognized the effects of perinatal maternal scFOS on offspring immune system, long after his birth [ 8 , 10 ]. Previous studies have demonstrated that the intestinal absorption of DON takes mainly place in the jejunum directly from the intestinal lumen to the apical side of the intestinal epithelium [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Maternal diet supplementation with prebiotics during pregnancy improves the offspring immune defenses by supporting the structural development of the gut mucosa [ 4 , 5 , 6 , 7 ]. Herein, we selected short-chain fructooligosaccharides (scFOS), a highly interesting prebiotic fiber, since we obtained previously very interesting results after maternal and/or direct FOS supplementation on mucosal immune system development and functionality [ 5 , 8 , 9 , 10 ]. Direct dietary FOS supplementation also promotes intestinal IgA secretion [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOS can also stimulate immune responses directly, through GALT (Peshev and Van den Ende, 2014). Molecules of fructans or polysaccharides may enhance the activation of specific cells of the immune system, as macrophages, dendritic cells, lymphocytes, or neutrophils, because pathogen-associated molecular patterns (PAMPs) are bonded with toll-like receptors (TLRs), which result in immunostimulation (Liu et al, 2011). For example, a yacón (which contains FOS) treatment increased TLR-4 expression in baby mice (Delgado et al, 2012;Velez et al, 2013).…”
Section: Immunological Activitymentioning
confidence: 99%
“…Indeed, in our experimental protocols, prebiotic supplementation was applied during a short postnatal period and completed before the start of solid food consumption, whereas the studies reporting programming effects of early supplementation with OS on the subsequent composition of the microbiota were based on longer-term supplements extending from the prenatal period (i.e. supplementation of gestating mothers) to complete weaning or even further [Fugiwara et al 2010;Le Bourgot et al 2019]. Whether the supplementation we applied was insufficiently early, insufficiently late or insufficiently sustained is difficult to establish on the sole basis of this comparison.…”
Section: Is Programming Of the Microbiota Subjected To A Particular Tmentioning
confidence: 99%